Music topics in a long dream series - Schredl, Michael (International journal of dream research, 2022)
Music is a very important part of human life in all known cultures. Within a series of 2,025 dreams recorded over more than 30 years by a female dreamer, the frequency and content of music dreams were analyzed. About 6% of her dreams included references to music, the high percentage of singing dreams compared to dreams with playing and instrument reflecting the dreamer’s daytime musical activities as she sang very often in church choirs but never learned to play an instrument. Moreover, about 9% of her music dreams were creative, that is, included genuinely new melodies the dreamer had never experienced before in her waking life. It would be very interesting to study whether dream incubation techniques (visualizing prior to sleep onset the intent of dreaming about new melodies/lyrics) can increase the frequency of creative music dreams.